Ett kommunikativt dubbelspel: en kvalitativ studie om motstridiga värden i en kontroversiell bransch - Lökken,Trine; Ekblom,Elin (2019)
This study aimed to increase the knowledge of how conflicting values within an organization are expressed in the external communication with the help of a text analysis. The study focused on two main communication channels: press releases and commercials that were analyzed with a rhetorical analysis of text and speech and a rhetorical analysis of visual messages. To increase the knowledge of the phenomenon a rhetorical framework was used, as well as theories about profit, social responsibility and paradoxes. The analysis pointed to the conclusion that two conflicting values within an organization can exist, and it does not necessarily affect the organization's ability to reach long-term strategic goals. The study concluded that the organization uses short-term communicative efforts to hide the double standard that the conflicting values creates within the organization.
Keywords: Strategisk kommunikation; extern kommunikation; kontroversiella branscher; spelindustrin; paradox; kvalitativ textanalys; motstridiga värden; vinstdrivande; ansvarstagande